(3CdMGf GdShGLY Hjf GdHGOj hGdeQGLYs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3abO cfJ bOjekG LeYJ cJGHj GdPj hSeJg HGdeLGQGI hGdoeMGRGI hbO CMHHJ GdBf Cf CLeY eG OGQ Hjfj hHjf aVdGA YUQj eeG HOCJ ajg hQGLYJ s
(3BNQgG (B:s
(3aefP aJMJ ajg GdHQhb LahfgG JHQbY efgG HGdMjG hJdqKeG hjdj gPG eNJGQGJ HNW eZGjQ s
(3GdNW eVHhWs
(3GfXQ CjVkG GdLRA GdChd HQbe (B54-75 (3COHs
(3YfhGf GdfSNI GdCdMGf GdShGLY Hjf GdHGOj hGdQGLYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B53 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B148s
Keywords: (3GdCOHs